HUBUNGAN DIPLOMATIK TURKI TERHADAP AMERIKA SERIKAT PASCA UPAYA KUDETA TURKI TAHUN 2016 - Hadi, Wan Saban; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The study seeks to analyze diplomatic relations between Turkey and the United States after a failed coup in Turkey on July 15, 2016. Relations between Turkey and the United States have worsened since the coup that took place in 2016, where the coup involved Fethullah Gullen who brought the United States in tensions that occur in Turkey. This is because Turkey is asking the United States to extradite Gullen to Turkey, but the United States is trying to protect Gullen. This has resulted in poor relations between Turkey and the United States.  The theory used in this study is Coercive Diplomacy, which explains the form of threats carried out by Turkey. The data sources used in this study are based entirely on secondary sources, including international and Turkish media coverage of the course of the coup. Includes various articles written by various experts / analysts about the incident. The perspective used in this study is the perspective of realism, and the level of analysis is the nation state. The research method used is a qualitative method. As a result of the involvement of the United States in the Turkish Coup, it caused a bad relationship, in which Turkey closed the United States Military base in Incirlik, establishing a closeness with Russia which became the enemy of United Stated politics and arrested a US state priest. However, it seems that the two countries will continue to continue Diplomatic Relations because of their interests and mutual needs. Keywords: Ekstradition, Coup, Diplomatic Relations, Turkey, United States